Implementasi Konsep Reproduksi Sehat Di Wilayah Kepulauan - Eka Fitri Amir; Yulianti Wulandari; Elvi Muniarsih; Indah Purnama sari; Yola Abdila Sianipar (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2023)
Panjang Island is one of the islands which is located about 60 KM from the City Center of Batam, Riau Islands. As an area that is not easy to access, various obstacles arise including health problems, especially healthy reproductive health. Reproductive health is defined as a healthy condition in terms of the reproductive system, functions and processes which includes mental, social and cultural health. The main problems of reproductive health in a region include the lack of information on reproductive health and the problem of shifting sexual behavior, especially in adolescents. Data from a study shows that knowledge of reproductive health, especially adolescents, tends to be lacking, namely 57.58% for male adolescents and 62.85% for female adolescents. Teenagers on an island still use limited health information sources and have limited access to regular health checks.